2011
DOI: 10.1371/journal.pone.0026529
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impacts of Experimentally Elevated Temperature on the Biological Composition and Molecular Chaperone Gene Expression of a Reef Coral

Abstract: Due to the potential for increasing ocean temperatures to detrimentally impact reef-building corals, there is an urgent need to better understand not only the coral thermal stress response, but also natural variation in their sub-cellular composition. To address this issue, while simultaneously developing a molecular platform for studying one of the most common Taiwanese reef corals, Seriatopora hystrix, 1,092 cDNA clones were sequenced and characterized. Subsequently, RNA, DNA and protein were extracted seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 48 publications
1
60
0
1
Order By: Relevance
“…In this regard, there is some variability in the observations related to stress effectors. Mayfield et al (2011) reported that thermal stress increased Seriatopora hystrix protein metabolism between 12 and 24 h, followed by a significant decrease Los datos se muestran como media ± EE (n= 3) Diferentes símbolos denotan diferencias significativas entre los tratamientos (P < 0,05). C 1 : tratamiento 7,85/7,95 pH; C 2: tratamiento: 7,60/7,70 pH; CC: tratamiento de control 8,00/8,40 pH at 48 h. By contrast, in the coral Acropora millepora, Hauri et al (2010) reported the persistence of extensive metabolism for up to 240 h after physicochemical stress.…”
Section: Discussionmentioning
confidence: 93%
“…In this regard, there is some variability in the observations related to stress effectors. Mayfield et al (2011) reported that thermal stress increased Seriatopora hystrix protein metabolism between 12 and 24 h, followed by a significant decrease Los datos se muestran como media ± EE (n= 3) Diferentes símbolos denotan diferencias significativas entre los tratamientos (P < 0,05). C 1 : tratamiento 7,85/7,95 pH; C 2: tratamiento: 7,60/7,70 pH; CC: tratamiento de control 8,00/8,40 pH at 48 h. By contrast, in the coral Acropora millepora, Hauri et al (2010) reported the persistence of extensive metabolism for up to 240 h after physicochemical stress.…”
Section: Discussionmentioning
confidence: 93%
“…Lo anterior ya había sido observado por Mayfield et al (2011) quienes además postularon que el simbionte aporta únicamente el 10% de los trascriptos de ARN en el coral Seriatopora hystrix. En este sentido también se observó que los morfotipos NCc y NJc presentaron las mayores relaciones de proteína/ADN, lo cual no ocurrió con ninguno de los corales restaurados, y podría ser el reflejo de que, posterior a un año de iniciada la restauración, los CO no alcanzaron el estado trascripcional que caracterizó a los especímenes de control.…”
Section: Discussionunclassified
“…The SHSTTE [12,14] and SHVTS [18,20] are described in prior works. Briefly, whole, unfragmented S. hystrix colonies from Houbihu were exposed to either the control (27 °C) or elevated temperature (30 °C) for 48 hr in the former, and RNAs, DNAs, and proteins were extracted from triplicate colonies housed within each of triplicate tanks at each of the two temperature treatments at each of four sampling times (6,12,24, and 48 hr; 18 samples/sampling time).…”
Section: The Experimentsmentioning
confidence: 99%
“…For instance, the common, Indo-Pacific reef-builder Seriatopora hystrix showed no mRNA-level molecular chaperone response when exposed for 2 d to 30 °C [12], a temperature hypothesized to ultimately elicit bleaching in this species based on observations made in Japan and elsewhere [13]. In fact, the expression of only 2 genes out of the 14 targeted (6 from Symbiodinium and 8 from the coral host), the cytoskeleton genes β-actin (actb) and α-tubulin (tuba), were determined by real-time PCR (qPCR) to be affected by temperature [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation